Revisiting Marxism in the Philippines: Selected Essays - Veneracion, Jaime B.; Rivera, Temario C.; Aguilar, Mila D.; Tadem, Eduardo C.; Malaluan, Nepomuceno A.; Guillermo, Ramon G. (Kasarinlan: Philippine Journal of Third World Studies; Vol 25 No 1-2 (2010): Political Economy of Ideas, 2010)
Reviews of Abinales, Patricio N. ed. 2010. Revisiting Marxism in the Philippines: Selected Essays. Manila: Anvil Publishing, Inc. 212 pp.
Keywords: Marxism, Philippines